Parents' and carers' views about emollients for childhood eczema: qualitative interview study. Issue 8 (19th August 2016) - Santer, M; Muller, I; Yardley, L; Lewis-Jones, S; Ersser, S; Little, P
Abstract : Objective: Leave-on emollients form the mainstay of eczema treatment, but adherence is poor. We aimed to explore parents'/carers' views on effectiveness and acceptability of leave-on emollients for childhood eczema through secondary analysis of data from 2 qualitative data sets. Setting: Study 1 recruited through mail-out from 6 general practices in southern England. Study 2 recruited from a feasibility trial of an intervention to support eczema self-care in 31 practices in the same area. Participants: Study 1 included 28 interviews with carers of children aged ≤5 years with eczema. Study 2 included 26 interviews with carers of children aged ≤5 years with eczema. Methods: Interviews followed semistructured guides: study 1 explored carers' understandings around eczema treatments in order to develop a web-based self-care support intervention; study 2 explored carers' understandings of eczema and eczema treatments after using the intervention. Interviews were carried out face to face or by telephone, audio-recorded and transcribed. Secondary analysis of data from both studies focused on views and experiences of emollient use. Data were analysed using an inductive thematic approach facilitated by NVivo V.10 software. Results: In study 1, most participants felt emollients improved eczema but held mixed views about long-term use to prevent flare-ups. In study 2, where carers had used the web-based intervention, all participants held positive views about long-term emollient use. In both studies, participants expressed a range of preferences about emollient 'thickness'; some felt that 'thick' emollients (ointments) were most effective, while others found these difficult to use. Carers described a process of 'trial and error', trying emollients suggested by professionals, friends and family, or bought over-the-counter. Carers expressed a need for understanding differences between products and their effective use. Conclusions: Providing a rationale for long-term emollient use and choice of emollients could help improve adherence and help families gain more rapid control of eczema.